CODE-SWITCHING AND CODE-MIXING ON JAPANESE TELEVISION ADVERTISING - Novitasari, Raden; Ainis, Syafiiah Alquratu; Putri, Aulia Aprianty Sukmana; Kamalia, Cici; Fridasari, Kusnaryati (CENTRAL ASIA AND THE CAUCASUS, 2022)
Language is an important instrument for communicating with other people. In everyday life, many foreign languages are found that are used in foreign products that speak foreign languages. This study discusses code-switching and code-mixing used in Japanese advertisements. This research uses the descriptive qualitative method. The data collection method used the listening method with the free-involved- talk (SBLC) listening technique. The technique used is the note-taking technique. The data source used is in the form of Japanese advertising videos contained on YouTube. The data analysis method used is the extra lingual equivalent method. The presentation of the results of data analysis in this study was carried out using an informal method. The data found are in the form of a transition from Japanese (kokugo) into a Kansai dialect and a transition from a Kansai dialect into Japanese (kokugo). Then for code-mixing, the data found are Kansai dialect insertion and English in Japanese sentences, as well as Japanese insertion in Chinese sentences, and English insertions in Japanese sentences and Japanese sentences insertion in English sentences.